The pseudokinase MLKL contributes to host defense against Streptococcus pluranimalium infection by mediating NLRP3 inflammasome activation and extracellular trap formation - Yu-Xin Lei; Yang Liu; Li-Hua Xing; Yu-Jing Wu; Xue-Yin Wang; Fan-Hua Meng; Ya-Nan Lou; Zhao-Guo Ma; Lin Yuan; Shui-Xing Yu (Virulence)
Host innate immunity plays a pivotal role in the early detection and neutralization of invading pathogens. Here, we show that pseudokinase mixed lineage kinase-like protein (MLKL) is required for host defence against Streptococcus pluranimalium infection by enhancing NLRP3 inflammasome activation and extracellular trap formation. Notably, Mlkl deficiency leads to increased mortality, increased bacterial colonization, severe destruction of organ architecture, and elevated inflammatory cell infiltration in murine models of S. pluranimalium pulmonary and systemic infection. In vivo and in vitro data provided evidence that potassium efflux-dependent NLRP3 inflammasome signalling downstream of active MLKL confers host protection against S. pluranimalium infection and initiates bacterial killing and clearance. Moreover, Mlkl deficiency results in defects in extracellular trap-mediated bactericidal activity. In summary, this study revealed that MLKL mediates the host defence response to S. pluranimalium, and suggests that MLKL is a potential drug target for preventing and controlling pathogen infection.